60.6k views
4 votes
How do you solve the equation above using substitution? Please show work :)

How do you solve the equation above using substitution? Please show work :)-example-1
User Chuysbz
by
5.0k points

1 Answer

2 votes

Answer:

the solution is (21/2, 19/2)

Explanation:

The first equation, x = y + 1, has already been solved for x. We can eliminate x in the second equatin by substituting y + 1 for x:

y = -(1/3)(y + 1) + 6

Let's eliminate fractions by multiplying all three terms by 3:

3y = y + 1 + 18

Combining like terms results in:

2y = 19, so that y = 19/2.

Substituting this 19/2 for y in the first equation, we get:

19/2 + 2/2 = x, or

x = 21/2

Thus the solution is (21/2, 19/2)

User Tyler Rash
by
4.6k points